1991
DOI: 10.1007/bf00227478
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a calcium ion stimulated-ATPase from goat spermatozoa

Abstract: The goat spermatozoa membranes isolated after treatment with octa (ethylene glycol) mono n-dodecyl ether (C12E8) followed by discontinuous sucrose density gradient centrifugation have been found to contain an ATPase that is stimulated by externally added Ca2+ only. The membrane fraction has also found to contain Mg(2+)-dependent Ca(2+)-ATPase activity, however the former activity is about 2 fold higher than the latter. The molecular weight of the enzyme is found to be about 97,000 on SDS-polyacrylamide gel. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Both, Mg 2+ -dependent Ca 2+ -ATPase-and Mg 2+ -independent Ca 2+ -ATPase activity have also been shown in goat (Sengupta et al 2007;Sikdar et al 1991) and bull spermatozoa (Sanchez-Luengo et al 2004;Triphan et al, 2007) as well as in microsomal membranes of rat testis (NagDas et al 1988). Sen and co workers (NagDas et al 1988;Sikdar et al 1991) showed similar results with a Mg 2+ -independent activity, higher than Mg 2+ -dependent activity in both goat spermatozoa and rat testis microsomal membranes. Whether or not Mg 2+ -independent-and Mg 2+ -dependent Ca 2+ -ATPase are two diVerent enzymes or identical molecules having the same or diVerent catalytic sites has not yet been elucidated.…”
Section: Functions Of Sperm Pmcamentioning
confidence: 87%
See 2 more Smart Citations
“…Both, Mg 2+ -dependent Ca 2+ -ATPase-and Mg 2+ -independent Ca 2+ -ATPase activity have also been shown in goat (Sengupta et al 2007;Sikdar et al 1991) and bull spermatozoa (Sanchez-Luengo et al 2004;Triphan et al, 2007) as well as in microsomal membranes of rat testis (NagDas et al 1988). Sen and co workers (NagDas et al 1988;Sikdar et al 1991) showed similar results with a Mg 2+ -independent activity, higher than Mg 2+ -dependent activity in both goat spermatozoa and rat testis microsomal membranes. Whether or not Mg 2+ -independent-and Mg 2+ -dependent Ca 2+ -ATPase are two diVerent enzymes or identical molecules having the same or diVerent catalytic sites has not yet been elucidated.…”
Section: Functions Of Sperm Pmcamentioning
confidence: 87%
“…Microsomal membranes of rat sperm were prepared according to Sikdar et al (1991). Epididymal sperm of 30 rats were pooled for one preparation of microsomal membranes.…”
Section: Preparation Of Microsomal Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsomal membranes of caput sperm, cauda sperm and capacitated cauda sperm were prepared as described previously (Sikdar et al. , 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Mg 2+ ‐dependent Ca 2+ ‐ATPase was measured using activity assays as described before using 5 μg sperm membrane fractions as sample (Sikdar et al. , 1991).…”
Section: Methodsmentioning
confidence: 99%